2018
DOI: 10.1080/00397911.2018.1535077
|View full text |Cite
|
Sign up to set email alerts
|

EfficientN-acylation of sulfonamides using cesium salt of Wells–Dawson heteropolyacid as catalyst: Synthesis of newN-acyl sulfonamides and cyclic imides

Abstract: Preparation of N-acyl sulfonamides (2a-j), (3a-m), (5a-f) and cyclic imides (3n-r)Under nitrogen atmosphere, a mixture of sulfonamide (1 mmol), acylating agent (2 mmol) and Cs 5 HP 2 W 18 O 62 catalyst (5 mmol %) in water (2 mL), was stirred at room temperature to obtain (2a-j), (3a-m), (5a-f) and under reflux for (3n-r). Reaction was monitored by TLC. After completion of the reaction, the catalyst was removed by filtration. The filtrate was washed by water (10 mL) and extracted with EtOAc (3x15 mL). The combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…It should be noted that the intermediate carboxylic acid ( 2′a ) was already obtained in our recent work in the presence of 5 mmol% Cs 5 HP 2 W 18 O 62 as catalyst and water as solvent. Also, we found that the second step does take place only in the presence of this catalyst, hence its high efficiency.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…It should be noted that the intermediate carboxylic acid ( 2′a ) was already obtained in our recent work in the presence of 5 mmol% Cs 5 HP 2 W 18 O 62 as catalyst and water as solvent. Also, we found that the second step does take place only in the presence of this catalyst, hence its high efficiency.…”
Section: Resultsmentioning
confidence: 84%
“…From the point of synthetic simplicity, one‐pot reaction could provide a far more efficient and straightforward access to the target molecules. In the connection with our recent work, we envisioned that carboxylic acid (2′) produced in situ from sulfonamide (a) and cyclic anhydride may react with 2‐amino benzothiazole to form new product (b) containing both scaffolds: sulfonamide and benzothiazole (Scheme ). Initially, a one‐pot, one‐step protocol at room temperature was examined, using the same already optimized conditions in previous report (5 mmol% Cs 5 HP 2 W 18 O 62 as catalyst and water as solvent) for the preparation of ( 2a ) from sulfonamide ( 1a ), succinic anhydride and 2‐amino benzothiazole as the model reaction (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations